Adsorption methods for arsenic removal in water bodies: a critical evaluation of effectiveness and limitations - Mojiri, Amin; Razmi, Elham; KarimiDermani, Bahareh; Rezania, Shahabaldin; Kasmuri, Norhafezah; Vakili, Mohammadtaghi; Farraji, Hossein (Frontiers in Water, 2024)
The presence of arsenic in water bodies poses a significant risk to both human health and the environment. Arsenic (As) contamination in water sources is a global environmental concern caused by both natural processes and human activities. Due to its toxic and persistent nature, arsenic has detrimental effects on ecosystems and human well-being. This study aimed to elucidate the mechanisms behind arsenic accumulation in water bodies. In aquatic environments, arsenic concentrations in drinking water have been reported as high as 1320 μg/L (Nicaragua), while groundwater levels exceeded 5000 μg/L (Thailand), and wastewater contained up to 134,000 μg/L (landfill leachate in Brazil). Furthermore, bioaccumulation of arsenic (μg/g) in fish species ranges from 0.4 (catfish in the Paraná River Delta, Brazil) to 362 (Pteromylaeus bovinus, Northern Adriatic Sea). Recent research has predominantly focused on removing arsenic from aqueous solutions through adsorption methods. Notably, nanoparticle adsorbents and graphene-based adsorbents demonstrate a high capacity for arsenic removal from water bodies.